An international study of internal audit function quality. Issue 3 (16th April 2018) - Jiang, Like; André, Paul; Richard, Chrystelle
Abstract : We investigate organisational and environmental factors that influence firms' incentives to develop high-quality internal audit functions (IAFs) by using a unique international sample formed by matching proprietary data from a global internal auditor survey with public data obtained from Worldscope. Concerning organisational factors, we find that a positive relationship exists between IAF quality and firm complexity and confirm that complex firms have a higher demand for monitoring and advising and, therefore, a greater need for formal controls. In addition, IAF quality is positively related to board monitoring and audit committee diligence but negatively associated with CEO power, which suggests that IAF quality is influenced by other key players in corporate governance. Regarding environmental factors, we document that IAF quality is positively associated with industry competition, which implies that a firm's incentive for a high-quality IAF is enhanced when confronted with greater environmental uncertainty. Furthermore, IAF quality has a significantly positive relationship with our self-constructed index of IAF requirements included in national corporate governance codes, which indicates that strong home-country corporate governance codes play a role in fostering IAF development.